Separation method and separation device

By scanning the frequency of ultrasonic waves in water, ultrasonic processing is solved, and the problem of low separation efficiency during reuse of batteries in the prior art is achieved, and efficient and accurate separation of current collector and electrode composite materials is achieved.

CN119452501APending Publication Date: 2025-02-14KK TOYOTA CHUO KENKYUSHO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380049994.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-06-19
Publication Date
2025-02-14

Smart Images

  • Figure CN119452501A_ABST
    Figure CN119452501A_ABST
Patent Text Reader

Abstract

This separation method comprises a separation step for separating a current collector (52) and an electrode mixture (54) by subjecting an electrode (50) to be treated, which is provided with the current collector (52) and the electrode mixture (54), to ultrasonic treatment in water (treatment liquid 32) while scanning the frequency of ultrasonic waves. A separation device (10) is provided with: a separation unit (60) that separates a current collector (52) and an electrode mixture (54) by ultrasonically treating an electrode (50) to be treated in water; and a control unit (15) that controls the separation unit (60) so that the separation unit (60) performs ultrasonic treatment while scanning the frequency of the ultrasonic waves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a separation method and a separation device. Background Art

[0002] In the past, as a method for separating the collector and the electrode composite material when recycling the battery, for example, the following methods have been proposed: immersing a small piece of the battery in a polar solvent such as water, alcohol, ketone, and subjecting it to mechanical stirring such as stirring and ultrasonic treatment for about 30 minutes to about 5 hours (Patent Document 1); a method of ultrasonically treating the electrode sheet under the condition that the power density of the front surface of the ultrasonic electrode is 50W / cm2 or more (Patent Document 2); a method of immersing the positive electrode in NMP at 50°C for 6 hours and then ultrasonically treating and grinding it (Non-Patent Document 1); a method of using NMP as a cleaning solution for the positive electrode and ultrasonically treating it at 70°C and 240 W for 90 minutes (Non-Patent Document 2); a method of crushing the electrode into 2~12 mm and ultrasonically treating it at 40 Hz and 100 W (Non-Patent Document 3), etc. Prior art literature Patent Literature

[0003] Patent Document 1: Japanese Patent No. 6828214 Patent Document 2: International Publication No. 2021 / 152302 Non-patent literature

[0004] Non-patent literature 1: H. Gao et al., ACS Appl. Mater. Interfaces 12, 2020, 51546-51554. Non-patent document 2: L.-P. He et al., Waste Management 46, 2015, 523-528. Non-patent document 3: J. Li et al., Chemosphere 77, 2009, 1132-1136. Summary of the invention Problems to be solved by the invention

[0005] However, in the above method, sometimes even if the electrode composite can be removed from the collector, the collector will be damaged, or even if the damage to the collector is suppressed, the electrode composite will remain in the collector. As a result, sometimes the collector components are mixed into the separated electrode composite, and sometimes the electrode composite components are mixed into the separated collector. In addition, sometimes a long time of processing is required, and pre-processing such as crushing is required, and the processing efficiency is low.

[0006] The present disclosure has been made to solve such a problem, and its main purpose is to separate a current collector and an electrode composite material efficiently and accurately. Means for solving problems

[0007] To achieve the above object, the present inventors have found that if an electrode is subjected to ultrasonic treatment in water while sweeping the frequency of ultrasonic waves, a current collector and an electrode composite material can be separated efficiently and accurately, thereby completing the present disclosure.

[0008] That is, the separation method disclosed in the present invention includes a separation step of subjecting a treatment target electrode including a current collector and an electrode composite material formed on the current collector to ultrasonic treatment while sweeping the frequency of ultrasonic waves in water to separate the current collector from the electrode composite material.

[0009] In addition, the separation device disclosed in the present invention comprises: a separation unit, which performs ultrasonic treatment in water on an electrode to be treated, which comprises a current collector and an electrode composite material formed on the current collector, to separate the current collector from the electrode composite material; and a control unit, which controls the separation unit so that it performs the ultrasonic treatment while scanning the frequency of the ultrasonic wave. Effects of the Invention

[0010] In the separation method and separation device disclosed in the present invention, the current collector and the electrode composite can be separated efficiently and with high precision. The reasons for obtaining such an effect are, for example, presumed as follows. In the separation method and separation device, instead of utilizing the chemical action of an organic solvent or an aqueous solution, the physical action of the cavitation effect using ultrasound is utilized, so that the current collector and the electrode composite can be separated with water without using an organic solvent or the like. Moreover, the surface tension of water is large, and it is easier to produce the cavitation effect than organic solvents such as NMP, so the current collector and the electrode composite can be separated efficiently. Moreover, since the ultrasonic treatment is performed while scanning the frequency of ultrasound in water, the energy distribution becomes appropriate, the damage to the current collector and the residue of the electrode composite are suppressed, and the current collector and the electrode composite can be separated with high precision. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is a diagram for explaining scanning and scanning cycles. Figure 2 This is a diagram to explain the scan width. Figure 3 It is an explanatory diagram schematically showing the structure of the separation device 10. Figure 4 It is an explanatory diagram showing the state of the ultrasonic device 20 before ultrasonic treatment. Figure 5 It is an explanatory diagram showing the state of the ultrasonic device 20 after ultrasonic treatment. Figure 6This is a photograph of the appearance of the electrode (collector foil) after ultrasonic treatment. Figure 7 This is a photograph of the appearance of the electrode (collector foil) after ultrasonic treatment. Figure 8 This is a flow chart showing an example of the separation method. Fig. 9 These are photographs of the appearance of the electrodes that were ultrasonically treated after various waiting times. Fig.10 It is a graph which shows the relationship between the waiting time and the combined material removal rate. Fig.11 This is a graph showing the relationship between the pH of water after ultrasonic treatment and the removal rate of the composite material. Fig.12 This is a graph showing the relationship between the amount of Li elution and the alloy removal rate. Fig.13 It is a graph showing the relationship between the Al dissolution amount and the alloy material removal rate. Fig.14 This is a graph showing the relationship between the composite material removal rate and the amount of Al in the composite material powder. DETAILED DESCRIPTION

[0012] [Separation method] The separation method disclosed in the present invention includes a separation step of subjecting an electrode to be treated by ultrasonic treatment to separate a current collector from an electrode composite material.

[0013] (Electrode to be treated) The electrode to be processed comprises a current collector and an electrode composite material formed on the current collector. The electrode to be processed is an electrode of a storage device such as a lithium-ion secondary battery, a plasma secondary battery, a double-layer capacitor, a hybrid capacitor, a simulated double-layer capacitor, and can also be taken out from a used storage device or a deteriorated storage device. The electrode to be processed can be a positive electrode or a negative electrode, or a bipolar electrode having a positive electrode composite material formed on one side and a negative electrode composite material formed on the other side. The electrode to be processed can remain in a state of being taken out from the storage device without breaking, for example, the area can be greater than 10 cm2, or greater than 30 cm2.

[0014] As the material of the current collector, aluminum, copper, titanium, stainless steel, nickel, iron, calcined carbon, conductive polymer, conductive glass, etc. can be cited. Among them, when the electrode to be processed is a positive electrode, the current collector preferably contains aluminum. As the shape of the current collector, foil, film, sheet, mesh, punched or expanded shape, lath body, porous body, foam body, fiber group formed body, etc. can be cited. The thickness of the current collector is, for example, 1 μm to 500 μm.

[0015] The electrode composite material may include an electrode active material, a binder material, and a conductive material as required, etc. The electrode composite material can be formed, for example, as follows: The electrode active material, the conductive material, and the binder material are mixed, an appropriate solvent is added to make a paste, which is coated on the surface of the current collector and dried, and compressed as required to increase the electrode density. The electrode composite material can be formed on one side of the current collector or on both sides.

[0016] Examples of the electrode active material contained in the electrode composite material include transition metal sulfides such as TiS2, TiS3, MoS3, FeS2, etc., lithium manganese composite oxides with a basic composition formula of Li(1 - x)MnO2 (0 < x < 1, the same below) or Li(1 - x)Mn2O4, etc., lithium cobalt composite oxides with a basic composition formula of Li(1 - x)CoO2, etc., lithium nickel composite oxides with a basic composition formula of Li(1 - x)NiO2, etc., lithium nickel cobalt manganese composite oxides with a basic composition formula of Li(1 - x)NiaCobMncO2 (a + b + c = 1), etc., lithium vanadium composite oxides with a basic composition formula of LiV2O3, etc., transition metal oxides with a basic composition formula of V2O5, etc., lithium iron phosphate, etc., active materials for the positive electrode of a lithium ion secondary battery. It should be noted that the "basic composition formula" means that other elements such as Al and Mg can be included. In addition, examples of the electrode active material include active materials for the positive electrode and / or negative electrode of capacitors, lithium ion capacitors, such as activated carbon, coke, vitreous carbon, graphite, non-graphitizable carbon, pyrolytic carbon, carbon fiber, carbon nanotube, polyacene, etc. In addition, examples of the electrode active material include inorganic compounds such as lithium alloys, tin compounds, carbonaceous materials capable of occluding and releasing lithium ions, composite oxides containing multiple elements, conductive polymers, etc., active materials for the negative electrode of a lithium ion secondary battery. Examples of the carbonaceous materials include coke, vitreous carbon, graphite, non-graphitizable carbon, pyrolytic carbon, carbon fiber, etc. Examples of the composite oxides include lithium titanium composite oxides, lithium vanadium composite oxides, etc. Examples of the conductive material contained in the electrode composite material include graphite such as natural graphite (flaky graphite, scaly graphite), artificial graphite, acetylene black, carbon black, Ketjen black, carbon whiskers, needle coke, carbon fiber, metals (copper, nickel, aluminum, silver, gold, etc.).

[0017] The binding material contained in the electrode composite plays the role of connecting and fixing the active material particles and the conductive material particles. It can be used as an organic binding material dissolved in an organic solvent, as an aqueous binding material dissolved in an aqueous solvent, or as a mixture thereof. As an organic binding material, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-containing resins such as fluorine rubber, or thermoplastic resins such as polypropylene and polyethylene, ethylene propylene diene monomer (EPDM) rubber, sulfonated EPDM rubber, natural butyl rubber (NBR), etc. can be listed. In addition, as an aqueous binding material, polyvinyl alcohol (PVA), styrene butadiene copolymer (SBR), polyethylene oxide (PEO), etc. can be listed, and carboxymethyl cellulose (CMC) can also be included. As an organic solvent, N-methylpyrrolidone, dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethylenetriamine, N, N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, etc. can be listed. As the aqueous solvent, water, various aqueous solutions, etc. can be cited. The conductive material contained in the electrode composite material can be, for example, one or a mixture of two or more of natural graphite (scaly graphite, flaky graphite), graphite such as artificial graphite, acetylene black, carbon black, Ketjen black, carbon whisker, needle coke, carbon fiber, metal (copper, nickel, aluminum, silver, gold, etc.), etc. Among them, as the conductive material, carbon black and acetylene black are preferred from the viewpoint of electronic conductivity and coating property.

[0018] (Separation process) In the separation step, the electrode to be processed is placed in water (i.e., the electrode to be processed is immersed in water) and ultrasonic treatment is performed while sweeping the frequency of the ultrasonic wave, thereby separating the current collector and the electrode composite material. The frequency sweeping is, for example, Figure 1 , Figure 2 As shown, the frequency is changed periodically.

[0019] In the separation process, the frequency of the ultrasonic wave may be periodically changed in a manner that reciprocates between the maximum frequency Fmax and the minimum frequency Fmin with the fundamental frequency F0 as the center (see Figure 1 and Figure 2 The fundamental frequency F0 is preferably set to be greater than or equal to 40 kHz and less than or equal to 240 kHz, and more preferably set to be greater than or equal to 80 kHz and less than or equal to 200 kHz.

[0020] In the separation process, when the frequency variation width centered on the fundamental frequency F0 is defined as the sweep width (refer to Figure 2 ), the sweep width can also be set within ±5kHz. That is, it can also be set to Fmax-F0≤+5kHz, Fmin-F0≥-5kHz. The sweep width can be within ±3kHz or within ±1kHz.

[0021] In the separation process, one scanning cycle is defined as the period from the rise of the wave with the minimum frequency Fmin to the fall of the wave with the maximum frequency Fmax (or half the period from the rise of the wave with the minimum frequency Fmin to the rise of the next wave with the minimum frequency Fmin) (see Figure 1 ), when the number of scan cycles per second is defined as the scan rate, the scan rate may be set to be 500 scan cycles / second or more. The scan rate may be 700 scan cycles / second or more, or 1000 scan cycles / second or more. In addition, the scan rate may be set to be 2000 scan cycles / second or less.

[0022] In the separation process, ultrasonic treatment is preferably carried out in the scope within 30 minutes, more preferably in the scope within 10 minutes, further preferably in the scope within 300 seconds, and further preferably in the scope within 180 seconds. In the separation process, ultrasonic treatment can be carried out more than 1 second, more than 5 seconds, and more than 15 seconds.

[0023] In the separation process, when the contact area between the current collector and the electrode composite material is set to A [cm2] and the output of the ultrasonic wave (output of the oscillator) is set to B [W], the ultrasonic treatment is preferably performed in a manner where the output density (power density) represented by B / A is 30 W / cm2 or less. The output density B / A is preferably 10 W / cm2 or less, and may also be 5 W / cm2 or less. The output density B / A may be 0.1 W / cm2 or more, and may also be 0.5 W / cm2 or more.

[0024] In the separation step, the ultrasonic treatment is preferably performed in a non-heating environment. In the separation step, for example, the ultrasonic treatment may be performed in a temperature range of 0°C to 30°C, or in a temperature range of 15°C to 25°C.

[0025] If the separation process described above is performed, the electrode composite is removed from the current collector, and the electrode composite removed from the current collector is dissolved and / or dispersed in water or precipitated in water. In this way, after the ultrasonic treatment, the current collector and the electrode composite are separated to obtain the current collector and composite water containing the electrode composite.

[0026] The proportion of the components of the collector (collector components) contained in the electrode composite separated in the separation process is preferably less than 0.18%, preferably less than 0.15%, and more preferably less than 0.1%. In addition, the proportion of the components of the electrode composite (electrode composite components) contained in the collector separated in the separation process is preferably less than 0.36%, preferably less than 0.3%, and more preferably less than 0.2%. "The proportion of the collector components contained in the electrode composite" can be set to a value obtained as follows, for example. First, water is removed from the composite water obtained in the separation process to obtain an electrode composite. The weight of the collector components in the obtained electrode composite is analyzed using inductively coupled plasma emission spectrometry (ICP). In addition, the weight ratio of the collector components to the weight of the electrode composite as the analysis object is obtained, and the weight ratio is used as the proportion of the collector components contained in the electrode composite. "The proportion of the electrode composite components contained in the collector" can be set to a value obtained as follows, for example. First, take out the electrode (collector) after ultrasonic treatment, rinse and dry it. For the electrode that has been rinsed and dried, the weight of the electrode composite component is analyzed by ICP to find the weight ratio of the electrode composite component relative to the weight of the electrode as the analysis object, and the weight ratio is used as the ratio of the electrode composite component contained in the collector. Alternatively, for the electrode that has been rinsed and dried, the weight ratio of the electrode composite component is found by the fundamental parameter method (FP method) of fluorescent X-ray analysis (XRF), and the weight ratio is used as the ratio of the electrode composite component contained in the collector. It should be noted that the ratio of the electrode composite component contained in the collector can be set to the ratio of the active material component contained in the collector, and when the active material contains a transition metal, it can also be set to the ratio of the transition metal contained in the collector (wherein, the transition metal contained in the active material). Transition metals may alloy with the collector components when the collector (Al, etc.) is redissolved, so it is preferred that there is less residue in the collector.

[0027] In the separation process, it is preferred to increase the removal rate of the electrode composite material from the collector (also referred to as the composite material removal rate). The composite material removal rate is preferably, for example, 90% or more, more preferably 97% or more, and further preferably 99% or more. In the separation process, it is preferred to reduce the pH of the water after ultrasonic treatment. Sometimes the components of the electrode to be treated are dissolved into the water and the pH of the water increases, but the smaller the degree, the more the composite material removal rate can be improved. The pH is, for example, preferably 11.5 or less, more preferably less than 11.4, and further preferably less than 11.2. The pH can be set to 6 or more, or 7 or more, or 10 or more. In the separation process, it is preferred to reduce the concentration of alkali metal components contained in the water after ultrasonic treatment. In the case where the active material of the electrode to be treated contains alkali metal components, the alkali metal components are sometimes dissolved in the water after ultrasonic treatment, but the lower the concentration of such alkali metal components, the more the composite material removal rate can be improved. The concentration of the alkali metal component is preferably 37.5 mg / L or less, more preferably less than 33 mg / L, and further preferably less than 32 mg / L. In the separation process, it is preferred to reduce the amount of the current collector dissolved in water per unit weight. The less the amount of the current collector dissolved in water, the more the composite material removal rate can be improved. The amount of the current collector dissolved in water is preferably less than 1.1%, more preferably less than 1.0%, and further preferably less than 0.9%. In the separation process, it is preferred to shorten the standby time for placing the electrode to be processed before ultrasonic treatment in water and standing by. The shorter the standby time, the more it is possible to suppress the dissolution of components contained in the electrode to be processed into water, so that the reaction of the dissolved components with the electrode composite material, the current collector, etc. is suppressed, and the composite material removal rate can be improved. The standby time is, for example, preferably less than 30 minutes, more preferably less than 5 minutes, and further preferably less than 3 minutes.

[0028] In the separation process, it is preferred to reduce the weight ratio of the collector component contained in the separated electrode composite material. This weight ratio is, for example, preferably less than 0.18%, more preferably less than 0.15%, and more preferably less than 0.1%. It should be noted that the higher the above-mentioned composite removal rate is, the smaller the weight ratio tends to be. Therefore, from the viewpoint of reducing this weight ratio, in the separation process, it is also preferred to reduce the above-mentioned pH, preferably reduce the concentration of the alkali metal component contained in the water after the above-mentioned ultrasonic treatment, preferably reduce the amount of the above-mentioned collector dissolved in water, and preferably shorten the above-mentioned standby time.

[0029] The electrode can be removed from the power storage device before the separation step. The electrode removed in the removal step can be used as the processing electrode without breaking it, or cut into an area of ​​10 cm2 or more, an area of ​​30 cm2 or more, etc. and used as the processing electrode.

[0030] After the separation step, a collector treatment step of washing and drying the collector separated in the separation step may be performed. The collector may be washed while the washing liquid flows, or may be immersed in the washing liquid. The washing liquid is preferably water. The collector may be dried by air drying, heating drying, vacuum drying, drum drying, spin drying, suction drying, infrared drying, or a combination thereof.

[0031] After the separation step, a composite material treatment step of filtering out the electrode composite material from the composite material-containing water obtained in the separation step and drying it can be performed. In the composite material treatment step, the electrode composite material can be rinsed during or after filtering the electrode composite material. The rinse liquid is preferably water. The electrode composite material can be dried by air drying, heating drying, vacuum drying, drum drying, rotary drying, suction drying, infrared drying, or a combination thereof. It should be noted that in the composite material treatment step, instead of filtering the electrode composite material, the electrode composite material can be separated from the composite material-containing water by solid-liquid separation methods such as centrifugal separation and evaporation to dryness.

[0032] The separation process, the collector treatment process, and the combined material treatment process may be carried out in a batch process or in a continuous process. When the separation process and the collector treatment process are carried out in a continuous process, a roll-to-roll process may be adopted. When the separation process is carried out in a roll-to-roll process, the electrode taken out in the taking-out process may be successively wound into a roll shape and used as the electrode to be treated.

[0033] It should be noted that, in this separation method, a current collector and an electrode composite are obtained, and therefore this separation method is both a method for producing a current collector and a method for producing an electrode composite.

[0034] [Separation device] The separation device disclosed in the present invention comprises: a separation section for performing ultrasonic treatment on the electrode to be processed to separate the current collector from the electrode composite; and a control section for controlling the separation section. In the separation device, the above-mentioned separation method can be performed, and the structure and conditions described in the above-mentioned separation method can also be applied. Alternatively, the separation device may comprise: a carry-in section for carrying the electrode to be processed into the separation section; and a carry-out section for carrying out at least one of the current collector and the electrode composite separated by the separation section from the separation section, and the control section controls the separation section, the carry-in section, and the carry-out section so that the ultrasonic treatment is performed in batches or continuously.

[0035] Hereinafter, a separation device 10 will be described as an example of a separation device. Figure 31 is an explanatory diagram schematically showing the structure of the separation device 10. The separation device 10 includes a separation unit 60, a carry-in unit 70, a collector carry-out unit 80 and a composite material carry-out unit 90 as carry-out units, and a control unit 15. In the separation device 10, an electrode 50 to be processed, which includes a collector 52 and an electrode composite material 54, is subjected to ultrasonic treatment to separate the collector 52 and the electrode composite material 54. The electrode 50 to be processed, the collector 52, and the electrode composite material 54 may be the same as the electrode to be processed, the collector, and the electrode composite material described in the separation method, respectively.

[0036] The separation unit 60 includes the ultrasonic device 20 and a pipe 62 for supplying water as the processing liquid 32 to the processing container 22 of the ultrasonic device 20. The pipe 62 is provided with a valve 62a to adjust the supply of the processing liquid 32 to the processing container 22 and the supply amount.

[0037] The ultrasonic device 20 performs ultrasonic treatment on the treatment target electrode 50 in water. Figure 4 , Figure 5 The ultrasonic device 20 is shown before and after ultrasonic treatment. The ultrasonic device 20 includes: a treatment container 22 that accommodates a treatment object electrode 50 and a treatment liquid 32; a vibrator 28 that is arranged to be in contact with the treatment container 22; and an oscillator 30 that supplies an electrical signal to the vibrator 28 to cause the vibrator 28 to oscillate. Water is used as the treatment liquid 32. The water may be tap water, distilled water, ion exchange water, or the like. The ultrasonic device 20 is configured such that water as the treatment liquid 32 is accommodated in the treatment container 22, and the treatment object electrode 50 is immersed in the treatment liquid 32 (see Figure 4 ), the oscillator 20 supplies power to the oscillator 18 to oscillate the oscillator 18, thereby ultrasonically treating the electrode 50 to be treated. By such ultrasonic treatment, the current collector 52 of the electrode 50 to be treated is separated from the electrode composite 54, and the current collector 52 and the composite material-containing treatment solution 33 (composite material-containing water) containing the electrode composite 54 are obtained (refer to Figure 5 ). In addition, the processing container 22 includes an inner tank 24 for accommodating the electrode 50 to be processed, a mounting table 25 for mounting the inner tank 24, and an outer tank 26 for accommodating the inner tank 24 and the mounting table 25. The inner tank 24 accommodates the processing liquid 32, and the outer tank 26 accommodates the ultrasonic propagation medium 36. The ultrasonic propagation medium 36 is, for example, water, and plays a role in propagating ultrasonic waves together with the processing liquid 32.

[0038] The oscillator 30 of the ultrasonic device 20 has a scanning function. The scanning function is, for example, Figure 1 , Figure 2 The ultrasonic device 20 is configured to sweep (periodically change) the frequency of the ultrasonic wave generated from the vibrator 28 by using the sweep function of the oscillator 30 .

[0039] The carrying-in section 70 is provided with a conveyor 72 for conveying the electrode 50 to be processed to the separation section 60. The carrying-in section 70 may also be provided with a take-out section (not shown) for disassembling the battery and taking out the electrode to be processed 50. The take-out section may also be provided with a discharge section for discharging the battery before disassembling the battery. In the discharge section, the battery may be forcibly discharged using an external power supply. In addition, the take-out section may also be provided with an inactivation section for inactivating the battery. In the inactivation section, the battery may be inactivated by heat treatment or by supplying an inactivating agent to the inside of the battery. In addition, the carrying-in section 70 may also be provided with a pre-treatment section (not shown) for treating the electrode taken out from the take-out section so that it is suitable for ultrasonic treatment in the separation section 60. In the pre-treatment section, the electrode taken out from the take-out section may also be cleaned and dried. In addition, in the pre-treatment section, the electrode taken out from the take-out section may be cut into an area of ​​10 cm2 or more and an area of ​​30 cm2 or more, and the electrode taken out from the take-out section may be wound into a roll in sequence. The carrying-in unit 70 only needs to be configured to carry the treatment target electrode 50 into the separation unit 60, and may include a conveying mechanism other than the conveyor 72. The removal unit and the pre-processing unit may be provided separately from the carrying-in unit 70.

[0040] The collector carrying-out section 80 includes: a robot arm 82 for carrying out the collector 52 separated by the separation section 60 from the processing container 22; and a conveyor 84 for carrying the collector 52 taken out by the robot arm 82. In addition, the collector carrying-out section 80 includes a rinsing device 86 for rinsing the collector 52 conveyed by the conveyor 84 and a drying device 88 for drying the collector 52 conveyed by the conveyor 84. The rinsing device 86 can be configured as follows: Figure 3 In that way, flushing is performed while the flushing liquid is allowed to flow, or it can be configured to be immersed in the flushing liquid for flushing. The flushing liquid is preferably water. The drying device 88 can also be configured to dry by air drying, heating drying, vacuum drying, drum drying, rotary drying, suction drying, infrared drying, or a combination thereof. It should be noted that the collector unloading section 80 only needs to be configured to be able to unload the collector 52 from the separation section 60. For example, either the robot arm 82 or the conveyor 84 can be omitted, or a transport unit other than the robot arm 82 and the conveyor 84 can be provided. In addition, the flushing device 86 and the drying device 88 can be provided separately from the collector unloading section 80, or can be omitted.

[0041] The composite material carrying-out section 90 is provided with: a pipe 92 for discharging the composite material-containing treatment liquid 33 obtained by the separation section 60 from the processing container 22; a filtering device 94 for filtering the electrode composite material 54 from the composite material-containing treatment liquid 33; a conveyor 96 for conveying the electrode composite material 54 filtered by the filtering device 94; and a drying device 98 for drying the electrode composite material 54 filtered by the filtering device 94. The pipe 92 is connected to the vicinity of the bottom of the processing container 22. A valve 92a is provided on the pipe 92, which can adjust the storage and discharge of the treatment liquid 32 and the composite material-containing treatment liquid 33 in the processing container 22. The drying device 98 can also be configured to dry by air supply drying, heating drying, vacuum drying, drum drying, rotary drying, suction drying, infrared drying, or a combination thereof. The composite material carrying-out section 90 can also be provided with a rinsing device for rinsing the electrode composite material 54. The rinsing device can be configured to supply a rinsing liquid to the filtering device 94 and rinse it together with the filtration, or it can be configured to separately rinse the electrode composite material 54 after filtration using the rinsing liquid. The rinse liquid is preferably water. It should be noted that the composite material carrying-out section 90 can be configured to carry out the electrode composite material 54 from the separation section 60, and any one of the pipe 92 and the conveyor 96 can be omitted, or a transport unit other than the pipe 92 and the conveyor 96 can be provided. In addition, the filtering separation device 94, the drying device 98, the rinse device, etc. can be provided separately from the composite material carrying-out section 90, or can be omitted. In addition, a solid-liquid separation device such as a centrifugal separation device and an evaporation drying device can be provided instead of the filtering device 94.

[0042] The control unit 15 is constructed as a microprocessor centered around a CPU, and in addition to the CPU, it also has a storage device, input and output ports, etc. (not shown in the figure). The control unit 15 is connected to the separation unit 60 (specifically, the oscillator 30, the valve 62a of the piping 62), the loading unit 70 (specifically, the conveyor 72), the collector unloading unit 80 (specifically, the robot arm 82, the conveyor 84, the flushing device 86, the drying device 88), and the combined material unloading unit 90 (specifically, the valve 92a of the piping 92, the filtering device 94, the conveyor 96, the drying device 98). The control unit 15 is configured to control the separation unit 60, the loading unit 70, the collector unloading unit 80, and the combined material unloading unit 90 so that the ultrasonic treatment is performed while scanning the frequency of the ultrasonic wave, and the ultrasonic treatment is performed in batches. The conditions for the ultrasonic treatment can be the same as those of the above-mentioned separation method (especially the separation step). In addition, in Figure 3 In the figure, for the convenience of illustration, only the connection between the control unit 15 and the oscillator 30 is illustrated, and the illustration of other connections is omitted.

[0043] An example of the operation of the separation device 10 is described. When an instruction to start the separation process is input to the control unit 15, the control unit 15 first controls the conveyor 72 to carry the electrode 50 to be processed placed on the conveyor 72 into the processing container 22 of the separation unit 60, and controls the valve 62a of the pipe 62 to supply a predetermined amount of water as the processing liquid 32 to the processing container 22. When the carrying-in of the electrode 50 to be processed and the supply of the processing liquid 32 are completed, the control unit 15 controls the oscillator 30 to supply an electrical signal to the oscillator 28 to oscillate the oscillator 28. Thus, the electrode 50 to be processed in the processing liquid 32 is subjected to ultrasonic treatment. During the ultrasonic treatment, the control unit 15 controls the oscillator 30 to use the scanning function of the oscillator 30, for example, to scan the frequency under the conditions that the basic frequency F0 is 40 kHz or more and 240 kHz or less, the scanning width is within ±5 kHz, and the scanning rate is 500 scanning cycles / second or more. In addition, the control unit 15 controls the oscillator 30, for example, to output power with an output density B / A of less than 30 W / cm2. In addition, the control unit 15 controls the oscillator 30 to perform ultrasonic treatment for a specified time in a range of, for example, more than 1 second and less than 30 minutes. Through such ultrasonic treatment, the collector 52 of the electrode 50 to be treated is separated from the electrode composite 54, and the collector 52 and the composite treatment liquid 33 containing the electrode composite 54 are obtained. Then, the control unit 15 controls the robot arm 82 to take out the collector 52 from the processing container 22 and place it on the conveyor 84, and controls the conveyor 84 to transport the collector 52. During the transportation of the collector 52, the control unit 15 controls the rinsing device 86 to rinse the collector 52, and then controls the drying device 88 to dry the collector 52. In addition, in parallel with the removal of the collector 52, the control unit 15 controls the valve 92a of the pipe 92 to discharge the composite material treatment solution 33 from the treatment container 22 and supply it to the filter device 94, so that the electrode composite material 54 is filtered from the composite material treatment solution 33. When the filtering of the electrode composite material 54 is completed, the control unit 15 controls the filter device 94 to discharge the electrode composite material 54 onto the conveyor 96, and controls the conveyor 96 to convey the electrode composite material 54. During the conveyance of the electrode composite material 54, the control unit 15 controls the drying device 98 to dry the electrode composite material 54. In this way, the separation of the collector 52 and the electrode composite material 54 of the electrode 50 to be processed is completed. In the separation device 10, by repeating such a series of actions, ultrasonic treatment is performed in a batch manner.

[0044] In addition, the separation device 10 may also be configured to include a pH detection unit for measuring the pH of the water in the treatment container 22, so that the pH of the water does not exceed a specified value (e.g., 11.5) to perform the separation process. In addition, the separation device 10 may also be configured to include an alkali metal component detection unit for detecting the alkali metal component contained in the water in the treatment container 22, so that the concentration of the alkali metal component contained in the water does not exceed a specified value (e.g., 37.5 mg / L) to perform the separation process. In addition, the separation device 10 may also be configured to include a collector component detection unit for detecting the collector component contained in the water in the treatment container 22, so that the amount of the collector component contained in the water does not exceed a specified value (e.g., 1.1%) relative to the unit weight of the collector to perform the separation process. In addition, the separation device 10 may also be configured to include a standby time measurement unit for measuring the above-mentioned standby time, and start the ultrasonic treatment within the specified standby time (e.g., within 30 minutes).

[0045] In the separation method and separation device described above, the current collector and the electrode composite can be separated efficiently and with high precision. The reasons for obtaining such an effect are, for example, presumed as follows. In the above-mentioned separation method and separation device, the physical action of the cavitation effect using ultrasound is utilized in the separation of the current collector and the electrode composite, so the current collector and the electrode composite can be separated with water. Moreover, the surface tension of water is large, and it is easier to produce cavitation effect than organic solvents, so the current collector and the electrode composite can be separated efficiently. Moreover, since the ultrasonic treatment is performed while scanning the frequency of ultrasound in water, the energy distribution becomes appropriate, the damage to the current collector and the residue of the electrode composite are suppressed, and the current collector and the electrode composite can be separated with high precision. It should be noted that in the above-mentioned separation method and separation device, since the physical action of the cavitation effect using ultrasound is used, regardless of whether the binding material contained in the electrode composite is aqueous or organic, the effect of being able to separate the current collector and the electrode composite with water can be obtained. In addition, since water is used as the treatment liquid, the treatment liquid is relatively cheap, the treatment liquid is easily removed from the separated current collector and electrode composite material, and the waste liquid is easily treated and has a small environmental load. Furthermore, since the current collector and the electrode composite material can be separated efficiently, even under high frequencies (low energy) such as 40kHz to 240kHz (preferably 80kHz to 200kHz), when the electrode to be treated is relatively large, and in a non-heating environment, the current collector and the electrode composite material can be separated with high precision.

[0046] In addition, the present disclosure is not limited to the above-mentioned embodiment at all, and can be implemented in various forms as long as it belongs to the technical scope of the present disclosure.

[0047] For example, in the above-mentioned embodiment, the separation device 10 includes the separation unit 60, the loading unit 70, the current collector unloading unit 80, and the composite material unloading unit 90, but one or more of the loading unit 70, the current collector unloading unit 80, and the composite material unloading unit 90 may be omitted. In addition, the separation unit 60 includes the ultrasonic device 20 and the piping 62, but the piping 62 may be omitted as long as the structure is configured to perform ultrasonic treatment on the treatment target electrode 50 in water.

[0048] In the above-mentioned embodiment, the separation device 10 performs ultrasonic treatment in a batch mode, but it can also perform ultrasonic treatment in a continuous mode. In this case, as a conveying means of the carrying-in section 70, a delivery device for delivering the electrode 50 to be processed wound into a roll can be provided instead of the conveyor 72. In addition, as a conveying means of the collector carrying-out section 80, a winding device for winding the collector 52 can also be provided instead of the robot arm 82 and the conveyor 84.

[0049] The present disclosure may also be shown as any one of the following [1] to

[14] . [1] A separation method includes a separation step of subjecting an electrode to be treated, the electrode comprising a current collector and an electrode composite material formed on the current collector, to ultrasonic treatment in water while scanning the frequency of ultrasonic waves to separate the current collector from the electrode composite material. [2] The separation method according to [1], wherein in the separation step, the ultrasonic treatment is performed on the treatment target electrode of the electrode composite material including a binding material including at least one of an organic binding material and an aqueous binding material. [3] The separation method according to [1] or [2], wherein in the separation step, the scanning is performed centered at a fundamental frequency of 80 kHz to 200 kHz. [4] The separation method according to any one of [1] to [3], wherein in the separation step, the scanning is performed with a scanning width within ±3 kHz around a fundamental frequency. [5] The separation method according to any one of [1] to [4], wherein in the separation step, the scanning is performed at a scanning rate of 500 scan cycles / second or more. [6] The separation method according to any one of [1] to [5], wherein in the separation step, the ultrasonic treatment is performed within a range of 10 minutes. [7] A separation method according to any one of [1] to [6], wherein, in the separation step, when the contact area between the collector and the electrode composite is set to A [cm2] and the output of the ultrasonic wave is set to B [W], the ultrasonic treatment is performed in a manner such that the output density represented by B / A is less than 10 W / cm2. [8] A separation method according to any one of [1] to [7], wherein the proportion of the collector component in the electrode composite separated in the separation process is less than 0.1%, and the proportion of the electrode composite component in the collector separated in the separation process is less than 0.2%. [9] The separation method according to any one of [1] to [8], wherein in the separation step, the ultrasonic treatment is performed under a non-heating environment.

[10] The separation method according to any one of [1] to [9], wherein the ultrasonic treatment is performed in a batch system or a continuous system.

[11] The separation method according to any one of [1] to

[10] , comprising a removal step of removing an electrode from an electrical storage device, wherein in the separation step, the electrode removed in the removal step is not broken but is used as the electrode to be treated and subjected to the ultrasonic treatment.

[12] A separation method according to any one of [1] to

[11] , comprising at least one of a collector treatment step and a composite material treatment step, wherein the collector treatment step rinses and dries the collector separated in the separation step, and the composite material treatment step separates and dries the electrode composite material from composite material-containing water containing the electrode composite material separated in the separation step.

[13] The separation method according to any one of [1] to

[12] , wherein the separation step is performed in a manner that satisfies one or more of the following (1) to (6): (1) In the separation step, the pH of the water after the ultrasonic treatment is set to 11.5 or less. (2) In the separation step, the concentration of the alkali metal component contained in the water after the ultrasonic treatment is set to 37.5 mg / L or less. (3) In the separation step, the amount of the current collector dissolved in the water per unit weight is set to 1.1% or less. (4) In the separation step, the electrode to be treated before the ultrasonic treatment is placed in the water and waits for a period of 30 minutes or less. (5) In the separation step, the weight ratio of the current collector component contained in the electrode composite material after separation is set to 0.18% or less. (6) In the separation step, the removal rate of the electrode composite material from the current collector is set to 90% or more.

[14] A separation device comprises: a separation unit, which performs ultrasonic treatment in water on an electrode to be treated, which comprises a current collector and an electrode composite material formed on the current collector, to separate the current collector from the electrode composite material; and a control unit, which controls the separation unit so that it performs the ultrasonic treatment while scanning the frequency of the ultrasonic wave. Example

[0050] Hereinafter, examples of implementing the separation method disclosed in the present invention will be described. In addition, Experimental Examples 1 to 14 and 19 are equivalent to Examples, and Experimental Examples 15 to 18 are equivalent to Comparative Examples. In addition, Experimental Examples 20 to 28 are equivalent to Examples.

[0051] 1. Experimental Example 1 to Experimental Example 19 [Preparation of electrodes to be treated] As electrodes to be treated, positive electrodes A to C and negative electrodes A to B shown below were prepared (see Table 1).

[0052] Positive electrode A is prepared by using N-methylpyrrolidone (NMP) to make a paste containing 92 wt% of LiNi1 / 3Co1 / 3Mn1 / 3O2 (NCM, manufactured by Toda Industries), 5 wt% of acetylene black (manufactured by Denka Co., Ltd.), and 3 wt% of polyvinylidene fluoride (PVDF, manufactured by KUREHA), and then applying the paste on both sides of a 20 μm thick aluminum collector foil.

[0053] Positive electrode B is prepared by using NMP to make a paste containing 92 wt% of LiNi0.8Co0.15Al0.05O2 (NCA, manufactured by Toda Industry), 5 wt% of acetylene black (manufactured by Denka Corporation), and 3 wt% of polyvinylidene fluoride (PVDF, manufactured by KUREHA), and then applying the paste on both sides of a 20 μm thick aluminum collector foil.

[0054] The positive electrode C was prepared by using NMP to make a paste containing 92 wt% of LiFePO4 (synthesized by our company), 5 wt% of acetylene black (manufactured by Denka Corporation), and 3 wt% of polyvinylidene fluoride (PVDF, manufactured by KUREHA), and then applying the paste on both sides of a 20 μm thick aluminum current collector foil.

[0055] Negative electrode A is made by mixing 98 wt% of graphite (OMAC1.5s, manufactured by Osaka Gas Chemical), 1 wt% of carboxymethyl cellulose (CMC, manufactured by Daicel), and 1 wt% of styrene butadiene copolymer (SBR, manufactured by JSR) into a paste with water, and then applying it on both sides of a 10 μm thick copper collector foil.

[0056] Negative electrode B is made by mixing a negative electrode composite material containing 98wt% graphite (SCMG-XR-s, manufactured by Showa Denko), 1wt% carboxymethyl cellulose (CMC, manufactured by Daicel), and 1wt% styrene butadiene copolymer (SBR, manufactured by JSR) with water into a paste, which is then applied to both sides of a 10μm thick copper collector foil.

[0057] [Ultrasonic treatment] In the ultrasonic treatment of Experimental Examples 1 to 19, an ultrasonic device (GCX-M-3FQ12 manufactured by Branson, output 500 W, outer tank capacity 20 L) was used. Figure 4 As shown, water is added to the outer tank 26, 40 mL of the treatment solution 32 is added to the glass container (inner tank 24), the electrode 50 to be treated is immersed therein, and ultrasonic waves are applied from the vibrator 28 under the outer tank 26. When the scanning function of the ultrasonic frequency is used, the scanning speed is set to 1000 scanning cycles / second. It should be noted that the power density is the value obtained by dividing the output of the ultrasonic device (500 W) by the contact area between the collector foil and the electrode composite layer (here, the electrode area × 2), and the power density is adjusted by adjusting the electrode area.

[0058] In Experimental Example 1, a 40 mm × 100 mm positive electrode A was used as the electrode to be treated. The treatment liquid was water, the ultrasonic frequency (fundamental frequency F0) was 170 kHz, the scanning condition (scan width) was ±1 kHz, the treatment time was 60 seconds, and the power density was 6.3 W / cm2.

[0059] In Experimental Example 2, a 40 mm×100 mm negative electrode A was used as the electrode to be treated. The treatment liquid was water, the ultrasonic frequency was 170 kHz, the scanning condition was ±1 kHz, the treatment time was 30 seconds, and the power density was 6.3 W / cm2.

[0060] In Experimental Example 3, the same procedure as in Experimental Example 1 was used except that the ultrasonic frequency was set to 120 kHz. In Experimental Example 4, the same procedure as in Experimental Example 3 was used except that the treatment time was set to 30 seconds. In Experimental Example 5, the same procedure as in Experimental Example 3 was used except that the power density was set to 3.1 W / cm2 by setting the electrode size to 40 mm×200 mm. In Experimental Example 6, the same procedure as in Experimental Example 3 was used except that the electrode to be treated was set to positive electrode B. In Experimental Example 7, the same procedure as in Experimental Example 3 was used except that the electrode to be treated was set to positive electrode C.

[0061] In Experimental Example 8, the same procedure as in Experimental Example 2 was used except that the ultrasonic frequency was set to 120 kHz. In Experimental Example 9, the same procedure as in Experimental Example 8 was used except that the treatment time was set to 10 seconds. In Experimental Example 10, the same procedure as in Experimental Example 8 was used except that the power density was set to 3.1 W / cm2 by setting the electrode size to 40 mm×200 mm. In Experimental Example 11, the same procedure as in Experimental Example 8 was used except that the treatment time was set to 60 seconds and the power density was set to 0.9 W / cm2 by setting the electrode size to 40 mm×715 mm. In Experimental Example 12, the same procedure as in Experimental Example 8 was used except that the electrode to be treated was set to negative electrode B.

[0062] Experimental Example 13 is the same as Experimental Example 1 except that the ultrasonic frequency is set to 80 kHz. Experimental Example 14 is the same as Experimental Example 2 except that the ultrasonic frequency is set to 80 kHz.

[0063] Experimental Example 15 is the same as Experimental Example 3 except that the scanning condition is set to no scanning. Experimental Example 16 is the same as Experimental Example 8 except that the scanning condition is set to no scanning.

[0064] Experimental Example 17 was the same as Experimental Example 3 except that the treatment liquid was NMP. Experimental Example 18 was the same as Experimental Example 17 except that the ultrasonic frequency was set to 40 kHz and the treatment time was set to 30 seconds.

[0065] Experimental Example 19 was the same as Experimental Example 1 except that the ultrasonic frequency was set to 40 kHz.

[0066] [Analysis of the ratio of the current collector foil components in the composite material] For Experimental Examples 1 to 19, the proportion of the collector foil component in the composite material was determined by inductively coupled plasma emission spectroscopy (ICP). Specifically, first, a membrane filter (Mercumyl pore JGWP0.45μm) was used to wash the solution containing the composite powder after ultrasonic treatment (containing the composite treatment solution) with pure water while performing pressure filtration, and dried at 50°C for 1 hour to obtain the composite powder. The weight of the collector foil component (aluminum or copper) in the composite powder was analyzed by ICP to determine the weight ratio of the collector foil component to the total weight of the composite powder. This was taken as the proportion of the collector foil component in the composite material. In addition, less than 0.1% was evaluated as "A (excellent)", more than 0.1% and less than 0.18% was evaluated as "B (good)", and more than 0.18% was evaluated as "F (unacceptable)".

[0067] [Analysis of the ratio of composite components in collector foil] For Experimental Examples 1, 3 to 7, 13, 15, 17 to 19 (positive electrode), the ratio of the composite material components in the collector foil was determined by inductively coupled plasma emission spectrometry (ICP). Specifically, first, the electrode after ultrasonic treatment was taken out, rinsed with water, and then dried naturally. For this electrode, the weight of the composite material components (transition metal components in the composite material, Ni, Co and Mn in the case of positive electrode A) was determined by ICP, and the weight ratio of the composite material components to the total weight of the electrode was determined. This was taken as the ratio of the composite material components in the collector foil. For Experimental Examples 2, 8 to 12, 14, and 16 (negative electrode), the ratio of the composite material components in the collector foil was determined by the fundamental parameter method (FP method) of fluorescent X-ray analysis (XRF). Specifically, first, the electrode after ultrasonic treatment was taken out, rinsed with water, and then dried naturally. For this electrode, the C amount (weight ratio) was determined within the analysis range of φ30 mm by the FP method of XRF. In addition, in the FP method of XRF, the detected elements are standardized as a whole to 100% and the quantitative value is calculated. In addition, the amount of C on one side and then on the surface layer is used as a standard. The amount of C thus obtained is used as the ratio of the composite material components in the collector foil. And, less than 0.2% is evaluated as "A (excellent)", 0.2% or more and less than 0.36% is evaluated as "B (good)", and 0.36% or more is evaluated as "F (unacceptable)".

[0068] [Results and Investigation] For Experimental Examples 1 to 19, the ratio of the current collector foil component in the composite material and the ratio of the composite material component in the current collector foil are summarized in Table 2. In addition, for Experimental Examples 8, 16, 3, and 15, the appearance photographs of the electrodes (current collector foils) after ultrasonic treatment are shown in Table 2. Figure 6 In addition, for Experimental Example 11, a photograph of the appearance of the electrode (collector foil) after ultrasonic treatment is shown in Figure 7 .

[0069] As shown in Table 2, it can be seen that in Experimental Examples 1 to 14 and 19, in which the treatment liquid is water and ultrasonic treatment using a scanning function is performed, the evaluation of the proportion of the collector foil component in the composite material and the proportion of the composite material component in the collector foil are both A or B, and the composite material and the collector foil can be separated with good precision. In addition, it can be seen that the composite material and the collector foil can be separated with good precision by ultrasonic treatment for a short time of less than 60 seconds. In addition, it can be seen that the composite material and the collector foil can be separated with good precision at a low power density of less than 6.3W / cm2. It can also be seen that the binder material (PVDF) of the positive electrode is organic, and the binder material (SBR) of the negative electrode is aqueous, but no matter which binder is used, the composite material and the collector foil can be separated with good precision by ultrasonic treatment using water.

[0070] On the other hand, in Experimental Examples 15 and 16 in which the treatment liquid was water and the ultrasonic treatment was performed without using the scanning function, a large amount of the composite material remained on the current collector foil.

[0071] In addition, in Experimental Examples 17 and 18, where the treatment liquid was NMP and ultrasonic treatment using a scanning function was performed, a large amount of composite material remained on the collector foil. It is speculated that since the organic binder is dissolved by NMP, the composite material in Experimental Examples 17 and 18, where the treatment liquid was NMP, was removed more than in Experimental Examples 3 and 19, where the treatment liquid was water, but in fact, the composite material was removed more when the treatment liquid was water. It is speculated that this is because the cavitation effect based on ultrasound is weak when NMP is used. In addition, in Experimental Examples 17 and 18, in Experimental Example 18, where the ultrasonic frequency was set to 40kHz, it can be seen that not only the proportion of composite material components in the collector foil increases, but also the proportion of collector foil components in the composite material increases, and the damage to the collector foil increases. In addition, in Experimental Example 19, the ultrasonic frequency was also set to 40kHz, but since the treatment liquid was water, the damage to the collector foil was suppressed compared to Experimental Example 18.

[0072] As described above, it is clear that the current collector and the electrode composite material can be separated efficiently and accurately by using water as the treatment liquid and performing ultrasonic treatment using a scanning function.

[0073]

[0074]

[0075] 2. Experimental Examples 20 to 28 However, before separation by the above-mentioned ultrasonic treatment, if the waiting time for immersing the electrode (especially the positive electrode) in water becomes longer, it is sometimes difficult to separate the composite layer. The reason is speculated as follows. By immersing the positive electrode in water, the water becomes alkaline due to the dissolution of the alkali metal components (such as lithium) contained in the positive electrode active material. It is speculated that because the water becomes alkaline, the collector components (such as aluminum) are dissolved into the water, and along with this, a compound is formed between the composite material and aluminum, which hinders separation and causes the composite material to remain on the collector. Therefore, in the following, in the method of separating the positive electrode collector and the positive electrode composite material by ultrasonic treatment, at least one of the waiting time [min] for placing the electrode to be treated before ultrasonic treatment in water and waiting, the pH of the water after ultrasonic treatment [-], the Li dissolution amount [mg / L] (the concentration of the alkali metal components contained in the water after ultrasonic treatment), and the Al dissolution amount [%] (the amount of the collector dissolved in water per unit weight) is adjusted to suppress the reduction in the removal rate of the composite layer. Figure 8 This is a flow chart showing an example of the separation method in this example.

[0076] [Electrode to be treated] As the electrode to be treated, the above-mentioned positive electrode A was used. The ratio of the composite material in the positive electrode was 74% by weight.

[0077] [Ultrasonic treatment] Using an ultrasonic device (GCX-M-3 FQ12 manufactured by Branson, output 500W, cleaning tank content 20L), water (pure water, pH 6) was added to the cleaning tank (outer tank), 50ml of aqueous solution was added to the glass container of the inner tank, and a positive electrode with an area of ​​40mm×100mm was placed therein for a predetermined period of time. Then, ultrasonic waves were applied from the vibrator under the outer tank. The conditions for ultrasonic treatment were a frequency of 120kHz, a scan width of ±1kHz, a scan speed of 1000 scan cycles / second, and a treatment time of 60 seconds.

[0078] [analyze] exist Figure 8The pH measurement of the treated water, the weight measurement of the positive electrode, and the ICP-OES analysis were performed at the timing shown. In the ICP-OES analysis, the Li concentration [mg / L] in the treated water, the Al concentration [mg / L] in the treated water, and the weight ratio [%] of aluminum in the composite powder were measured using an inductively coupled plasma emission spectrometer (ICP-OES, PS3520 UVDDII II manufactured by Hitachi High-Technologies Corporation). And, the measured Li concentration [mg / L] was taken as the Li dissolution amount. In addition, the dissolution amount [%] of the collector (Al) per unit weight in water was derived from the measured Al concentration [mg / L], and it was taken as the Al dissolution amount. In addition, the Al amount in the composite was calculated in the same manner as the above-mentioned [Analysis of the ratio of the collector foil component in the composite]. In addition, the composite removal rate was derived from the weight measurement results. The composite material removal rate is the value expressed as a percentage by dividing the weight reduction rate of the positive electrode before and after the separation process by the weight ratio of the composite material in the positive electrode, 74%. If the Al foil is damaged and its weight is reduced, this part is also included in the composite material removal rate in the calculation.

[0079] [Results and Investigation] Table 3 summarizes the immersion waiting time in water [min], pH after ultrasonic treatment, Li dissolution amount [mg / L], Al dissolution amount [%], Al amount in composite powder [%], composite removal rate [%] and composite removal rate determination results of Experimental Examples 20 to 28. The determination criteria for composite removal rate are as follows: A is set for 99% or more, B is set for 97% or more and less than 99%, C is set for 90% or more and less than 97%, D is set for 80% or more and less than 90%, and F is set for less than 80%. In Table 3, the immersion waiting time "immediately" means that ultrasonic waves are applied immediately after the positive electrode is immersed. Experimental Example 20 is an experimental example in which the same treatment as Experimental Example 3 was performed. It should be noted that for Experimental Examples 20 to 28, the case where holes and gaps were observed on the foil by visual inspection was judged as "damaged", and the case where they were not observed was judged as "undamaged", and the damage of the collector was judged, but all were "undamaged".

[0080] Fig. 9 These are photographs of the appearance of the electrodes that were ultrasonically treated after various waiting times. Fig.10 It is a graph which shows the relationship between the waiting time and the combined material removal rate. Fig.11 This is a graph showing the relationship between the pH of water after ultrasonic treatment and the removal rate of the composite material. Fig.12 This is a graph showing the relationship between the amount of Li elution and the alloy removal rate. Fig.13 It is a graph showing the relationship between the Al dissolution amount and the alloy material removal rate. Fig.14 is a graph showing the relationship between the removal rate of the composite material and the amount of Al in the composite material powder. Figure 9~Figure 14As shown in Figure 2, in Experimental Examples 20 to 28, a high material removal rate of more than 90% was achieved. Fig.10 As shown, the shorter the waiting time, the higher the removal rate of the combined material. More preferably, when the waiting time is less than 30 minutes, the removal rate of the combined material is more than 90%, when the waiting time is less than 5 minutes, the removal rate of the combined material is more than 97%, and when the waiting time is less than 3 minutes, the removal rate of the combined material is more than 99%. Fig.11 As shown in the figure, the lower the pH of the water after ultrasonic treatment, the higher the composite material removal rate. More preferably, the composite material removal rate is 90% or more when the pH is below 11.5, 96% or more when the pH is less than 11.4, and 99% or more when the pH is less than 11.2. Fig.12 As shown, the lower the Li dissolution amount, the higher the composite material removal rate. More preferably, when the Li dissolution amount is less than 37.5 mg / L, the composite material removal rate is more than 90%, when the Li dissolution amount is less than 33 mg / L, the composite material removal rate is more than 97%, and when the Li dissolution amount is less than 32 mg / L, the composite material removal rate is more than 99%. Fig.13 As shown, the lower the Al dissolution amount, the higher the composite material removal rate tends to be. More preferably, the composite material removal rate is above 90% when the Al dissolution amount is less than 1.1%, the composite material removal rate is above 97% when the Al dissolution amount is less than 1.0%, and the composite material removal rate is above 99% when the Al dissolution amount is less than 0.9%. It can be seen that by adjusting at least one of the standby time, the pH of the water after ultrasonic treatment, the Li dissolution amount [mg / L], and the Al dissolution amount [%], the reduction in the removal rate of the composite material layer can be suppressed. In addition, as Fig.14 As shown, the Al content in the composite powder tends to decrease as the composite removal rate increases. More preferably, the Al content in the composite powder is less than 0.18% when the composite removal rate is above 90%, and the Al content in the composite powder is less than 0.10% when the composite removal rate is above 99%.

[0081]

[0082] This application claims priority based on Japanese Patent Application No. 2022-121627 filed on July 29, 2022, the contents of which are incorporated herein by reference in their entirety. Industrial Applicability

[0083] The present disclosure can be used in the field of battery industry. Description of Reference Numerals

[0084] 10 separation device, 15 control unit, 20 ultrasonic device, 22 processing container, 24 inner tank, 25 mounting table, 26 outer tank, 28 vibrator, 30 oscillator, 32 processing liquid, 33 composite material processing liquid, 36 ultrasonic propagation medium, 50 processing object electrode, 52 collector, 54 electrode composite material, 60 separation unit, 62 piping, 62a valve, 70 loading unit, 72 conveyor, 80 collector unloading unit, 82 robot arm, 84 conveyor, 86 flushing device, 88 drying device, 90 composite material unloading unit, 92 piping, 92a valve, 94 filtering device, 96 conveyor, 98 drying device.

Claims

1. A separation method comprising: In the separation step, an electrode to be treated, which includes a current collector and an electrode composite material formed on the current collector, is subjected to ultrasonic treatment in water while sweeping the frequency of ultrasonic waves, thereby separating the current collector from the electrode composite material.

2. The separation method according to claim 1, wherein In the separation step, the ultrasonic treatment is performed on the treatment target electrode including the electrode composite material including a binding material including at least one of an organic binding material and an aqueous binding material.

3. The separation method according to claim 1 or 2, wherein: In the separation step, the scanning is performed with a fundamental frequency of 80 kHz to 200 kHz as the center.

4. The separation method according to claim 1 or 2, wherein: In the separation step, the scanning is performed with a scanning width within ±3 kHz around the fundamental frequency.

5. The separation method according to claim 1 or 2, wherein: In the separation step, the scanning is performed at a scanning rate of 500 scanning cycles / second or more.

6. The separation method according to claim 1 or 2, wherein: In the separation step, the ultrasonic treatment is performed within 10 minutes.

7. The separation method according to claim 1 or 2, wherein: In the separation step, when the contact area between the collector and the electrode composite is set to A [cm2] and the output of the ultrasonic wave is set to B [W], the ultrasonic treatment is performed in a manner such that the output density represented by B / A is less than 10 W / cm2.

8. The separation method according to claim 1 or 2, wherein: The proportion of the collector component in the electrode composite separated in the separation step is less than 0.1%, and the proportion of the electrode composite component in the collector separated in the separation step is less than 0.2%.

9. The separation method according to claim 1 or 2, wherein: In the separation step, the ultrasonic treatment is performed in a non-heating environment.

10. The separation method according to claim 1 or 2, wherein: The ultrasonic treatment is performed in a batch mode or a continuous mode.

11. The separation method according to claim 1 or 2, wherein: The separation method includes a step of removing the electrode from the electrical storage device, In the separating step, the electrode taken out in the taking out step is not broken but is subjected to the ultrasonic treatment as the electrode to be treated.

12. The separation method according to claim 1 or 2, wherein: The separation method includes at least one of a collector treatment process and a composite material treatment process, wherein the collector treatment process rinses and dries the collector separated in the separation process, and the composite material treatment process separates and dries the electrode composite material from composite material-containing water contained in the electrode composite material separated in the separation process.

13. The separation method according to claim 1 or 2, wherein: The separation step is performed in a manner that satisfies one or more of the following (1) to (6): (1) in the separation step, the pH of the water after the ultrasonic treatment is set to 11.5 or less, (2) in the separation step, the concentration of the alkali metal component contained in the water after the ultrasonic treatment is set to 37.5 mg / L or less, (3) in the separation step, the amount of the current collector dissolved in the water per unit weight is set to 1.1% or less, (4) In the separation step, the electrode to be treated before the ultrasonic treatment is placed in the water and waits for a period of 30 minutes or less. (5) in the separation step, the weight ratio of the current collector component contained in the separated electrode composite material is set to 0.18% or less, (6) In the separation step, the removal rate of the electrode composite material from the current collector is set to 90% or more.

14. A separation device comprising: a separation unit for subjecting a treatment target electrode including a current collector and an electrode composite material formed on the current collector to ultrasonic treatment in water to separate the current collector from the electrode composite material; and The control unit controls the separation unit so as to perform the ultrasonic treatment while scanning the frequency of the ultrasonic wave.

Citation Information

Patent Citations

  • Fault detection device for engine fuel system

    JP2022121627A

  • Electrode separation by sonication

    WO2021152302A1